System quality, user satisfaction, and perceived net benefits of mobile broadband services - Eunice Hsiao-Hui Wang; Chao-Yu Chen (International Telecommunications Society (ITS), 2011)
The continued decline of voice revenues is pushing mobile operators in Taiwan turn into data and content services for exploring new revenue opportunities and raising ARPU. This study aims to discuss the critical determinants of the internet user's adoption of 3.5G mobile broadband services in Taiwan. The theoretical framework employed in the study is Information System Success Model (DeLone & McLean, 2003; Chae et al.,2002), which is operationally defined with mobile web-services measurement scales. The study attempts to identify how the system quality of 3.5G mobile broadband services affects the customer satisfaction and their perceived net benefit. With the affordable mobile broadband connectivity, 3.5 G access or HSDPA in Taiwan has played a major role in the burgeoning mobile Internet market. HSDPA (High Speed Downlink Packet Access) could be viewed as an advanced version of WCDMA wireless network. HSDPA ideally provides mobile data services up to 14.4 Mbps for the downlinks and up to 5.8 Mbps for the uplinks. According to TWNIC, the number of cell phone subscribers in Taiwan has grown up to 23 million by March 2009 with a 100% penetration rate Yet, among cell phone subscribers there were only 1.6 million users adopting mobile broadband services.
Keywords: 330; Mobile Broadband Services; IS Success Model; Customer Satisfaction; Net Benefits